Does Experience of Being a National Athlete Support Woman Resilience? A Qualitative Study of Former Female Athletes (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2025)
Sport is believed to provide positive psychological benefits and support positive personal growth, including resilience, the ability to deal with stress. However, the research exploring positive benefits obtained by female athletes, especially after they retired as athletes, is scarce. This research aimed to comprehend whether the experience of being a national athlete supports the formation of resilience in women even after they retired as athletes. The research used a qualitative approach with semi-structured interview data collection methods. Participants were 7 former female athletes who had represented Indonesia at international events. All of them were retired and working as professionals. Interviews were transcribed and analyzed using content analysis. The results of this research showed that the experience of pursuing a career to achieve international achievements had profound impacts on their life, especially when facing daily challenges in the workplace and at home which contribute to their resilience. Three dominant themes were articulated from the analysis, including discipline and self-regulation (such as having a regular scheduled routine, keeping to the time for every activity, and preparing early to achieve better results, affecting their succession in their current profession), the ability to reflect on emotions and control negative emotions (such as when life challenges cause emotional turmoil, past experience in sports at the national-international level provides reference to be competent in recognizing self-weaknesses leading to manage emotions in retrospective way), and opportunities for career achievements brought by involvement in sports at the national level, including the ‘dream career’, and wider networking access for career advancement and social supports. Considering the positive highlights of this results, it is recommended that policymakers support female participation more in elite sports and provide supportive environments for female athletes.